Encouraging post-stroke patients to be active seems possible: results of an intervention study with knowledge brokers. Issue 17 (13th August 2016) - Willems, Mia; Schröder, Carin; van der Weijden, Trudy; Post, Marcel W.; Visser-Meily, Anne M.
Abstract: Purpose : Although physical activity and exercise for stroke patients is highly recommended for fast recovery, patients in hospitals and rehabilitation centres are insufficiently encouraged to be physically active. In this study, we investigated the impact of knowledge brokers (KBs), enterprising nurses and therapists, on health professionals' (HP) performance to encourage stroke inpatients to be physically active. Method : This multicenter intervention study used a pre–post test design. Two or three KBs were trained in each stroke unit of 12 hospitals and 10 rehabilitation centres in The Netherlands. Questionnaires were completed by patients and HPs before and after the KB-intervention. The primary outcome was encouragement given by HPs to their patients to be physically active, as reported by patients and HPs. Results : After the KB-intervention, many more patients (48%; N =217) reported at least some encouragement by HPs to be physically active than before (26%; N =243, p <0.000). HPs ( N =288) on an average reported encouraging patients more often after the intervention, but this difference was significant only for occupational therapists and KBs. Conclusions : Based on patient's reports of HP behaviour, the KB-intervention appears effective since more patients felt encouraged to be physically active after the intervention compared to before. Replication of this study in an experimental design is needed to allow causal inferences. Implications for rehabilitation: We advise rehabilitation teams to make use of knowledge brokers (KBs), since the KB-intervention was shown to increase the encouragement felt by stroke patients to be physically active. It seems worthwhile to involve physicians, nurses and patients' families more frequently in efforts to encourage stroke patients to be physically active.